An experimental study of two methods of teaching multiplication of fractions - Ibe, Milagros D. 1931- (s.n.], 1965)
Two comparable sixth grade classes of the Maquiling School in College, Laguna are exposed to differentiated methods of teaching fractions to determine which of the two methods will lead to better achievement in fraction multiplication and mental arithmetic, and longer retention of skills in fraction addition and multiplicaton. In the control group, drill method was used. The experimental group, on the other hand, used meanings, visual aids, logical statements and inductive reasoning.